The war on welfare and the war on asylum - Jon Burnett (Race & Class, 2015)
This articles examines the parallels between the UK government’s ‘war’ on welfare and ‘war’ on asylum, in terms of the creation of widespread destitution and the rhetoric which punishes those depicted as ‘bogus’. In both cases, large private corporations now control people’s fates, whilst a ‘disturbed morality’ encourages the wider public to support such a coercive system and inform on our neighbours.